Occupational risk factors for multiple sclerosis: a systematic review with meta-analysis - Vitturi, Bruno Kusznir; Montecucco, Alfredo; Rahmani, Alborz; Dini, Guglielmo; Durando, Paolo (Frontiers in Public Health, 2023)
We decided to conduct the first systematic review with meta-analysis to provide the highest level of up-to-date evidence on the occupational risk factors for Multiple Sclerosis.A systematic, comprehensive literature search was performed in four electronic academic databases. We included any case-control study that enrolled working-age subjects and compared the proportion of MS cases with controls who were not exposed to an occupational risk factor. The primary outcome was the occurrence of MS. The quality assessment was performed with the Critical Appraisal Checklist for Case Control Studies, developed, and validated by the Joanna Briggs Institute. All the selection process was also carried out by two independent and previously trained researchers.Overall, the total sample included 19004 people with MS and 4164162 controls. Agricultural workers (OR = 1.44, 95% CI 1.13 -1.83), offshore workers (OR = 3.56, 95% CI 2.74 -4.61) and hairdressers (OR = 8.25, 95% CI 1.02 -66.52) were associated with a higher risk of being diagnosed with MS. In parallel, workers exposed to toxic fumes from oil wells (OR = 16.80,), lowfrequency magnetic fields (OR = 1.71, 95% CI 1.03 -2.72) and pesticides (OR = 3.17, 95% CI = 2.53 -3.99) also had an increased likelihood of having MS.Our study has the potential to influence more assertive public policies. Nevertheless, future studies on how the occupational setting may contribute to the incidence of MS are highly recommended.